Can 60 days of feeding lead to increased fitness for transport in cull dairy cows? - N. Berdusco; D. Kelton; D. Haley; K.M. Wood; T.F. Duffield (Journal of Dairy Science, 2024)
ABSTRACT: The welfare of cull cows during transport to slaughter is a current concern in the Canadian dairy industry. Cull cows sold through auction often have a high prevalence of lameness, low BCS, hock lesions, and udder engorgement. To evaluate whether drying off and feeding cull dairy cows before transport can mitigate these challenges, 45 cows designated for culling were randomly assigned to either be fed for 60 d after being dried off (fed group; n = 24) or to serve as controls by being sent directly to slaughter (direct group; n = 21). Two fed group cows were removed for health reasons before completing the feeding period. Both fed group and direct group cows were assessed for locomotion (5-point scale), BCS (5-point scale), hock lesions (3-point scale), udder engorgement (3-point scale), and BW at the time of enrollment. Fed group cows, locomotion, BCS, hock, and udder engorgement scores were assessed weekly until slaughter. Weights of the fed group cows were measured again the day before slaughter. Mixed linear regression models were used to assess continuous outcomes BCS and weight. Mixed logistic regression models were used to assess dichotomous outcomes presence of hock lesions and lameness. Fed group cows gained an average of 116.9 kg over the feeding period (SE ± 8.20). Fed group cows had an average weight at slaughter of 834.2 kg, whereas direct group cows' average weight was 767.3 kg (SE ± 26.8). The fed group cows' average BCS at the start of the trial was 2.4, and at slaughter was 3.6, with an average gain of 1.2 BCS points. At slaughter, the proportion of udders involuted in the fed group was 45.1% (10/22) and in the direct group cows, was 0% (0/21). No differences were found in locomotion or hock lesions between the fed group and direct groups. It is important to weigh potential benefits for the fed group cows with the fact that direct group cows did not endure a drying off procedure, nor were they placed at risk of potential adverse health events. However, despite these potential limitations, due to the improved BCS and udder engorgement scores, cows fed for 60 d may be better prepared for the transportation to slaughter, as well as sell for a higher price due to increased BW and body condition.